Evaluation of antioxidant prophylactic effects of parsley (Petroselinum crispum) on sepsis following cecal ligation and puncture - Alaadin Polat; Azibe Yıldız; Ahmet Kadir Arslan; Kevser Tanbek; Onural Özhan; Hakan Parlakpınar; Nigar Vardı; İhsan Kulaksiz; Furkan Çağan; Yahya Atayan (Atatürk University, 2024)
Objective: Sepsis causes the release of free oxygen radicals that disrupt membrane integrity, and damage to Mitochondria due to the production of free oxygen radicals and oxidation leads to exacerbation of sepsis, Cecal ligation and puncture (CLP) in rats mimics the characteristics and course of clinical sepsis (Hubbard et al., 2005). Methods: We evaluated the antioxidant effects of Petroselinum crispum (Pc) in a cecal ligation and puncture (CLP)-induced rat sepsis model, in a rat model of sepsis caused by cecal ligation and puncture (CLP). Wistar albino rats were separated into four groups of eight groups: a sham group with incised and sutured abdomens; a Pc extract (PcE) group, which was given 2 g/kg parsley extract for 14 days by gastric gavage; a CLP group, which was subjected to sepsis caused by CLP; and a PcE + CLP group, which was given parsley extract for 14 days. PcE was given for 14 days, after which sepsis was induced via the CLP procedure. The groups were compared in terms of hemogram, biochemical and histological characteristics. Results: The administration of PcE before CLP-induced sepsis increases neutrophil counts, PLTs and TASs, which decrease with sepsis, and decreases biochemical changes (BUN, AST, ALT, LDH, TOS, and OSI), which increase with sepsis, to protect against sepsis. Compared with that in the CLP group, the severity of intestinal infiltration was significantly lower in the PcE + CLP group; however, the degree of epithelial damage in the PcE + CLP group was similar to that in the CLP group. In the PcE + CLP group, the crypt and villus lengths were greater, and the decrease in Paneth cell degranulation intensity was greater than that in the CLP group. Conclusion: Additionally, the morphology of the cells in the PcE + CLP group was similar to that in the sham group. PcE has potential as a prophylactic agent for sepsis.